The lord of the rings. The return of the king [videorecording (Blu-Ray)] - Osborne, Barrie; Walsh, Fran, 1959-; Jackson, Peter, 1961-; Boyens, Philippa; Wood, Elijah, 1981-; McKellen, Ian; Tyler, Liv; Mortensen, Viggo, 1958-; Astin, Sean; Blanchett, Cate, 1969-; Rhys-Davies, John; Hill, Bernard, 1944-; et al. (New Line Home Entertainment, 2010)
As the remains of the fellowship prepare for battle, Frodo and Sam, with Gollum in tow, make their way to Mount Doom to destroy the One Ring.